KORELASI ANTARA PELATIHAN JABATAN FUNGSIONAL AUDITOR OLEH BPKP, KOMPETENSI AUDITOR DAN JENJANG JABATAN FUNGSIONAL AUDITOR TERHADAP KINERJA AUDITOR PADA INSPEKTORAT JENDERAL DEPARTEMEN DAN LEMBAGA PEMERINTAHAN NON DEPARTEMEN - Aang Syahdina (Universitas Bunda Mulia, 2017)
Since the economic crisis in 1997, Indonesia until this time hasn’t show any significant changes, it is indicated by the government performance that had shown many corruption, collusion, and nepotism, which can’t be detected by Government Internal Auditor. Based on that case, now a day government has a commitment to say no to corruption, collusion and nepotism in every aspect to create good governance. This is a main issue for Auditor since auditor will have a big responsibility in the future and it is decided by their commitment and professionalism. As mention above, writer thought that it’s necessary to do this research which is related with auditor performance, so that it will have a complete perception about every aspect which is affecting the auditor performance. The variable which include in this research is the correlation between functional Auditor training by BPKP, auditor competencies, Auditor functional position, with auditor performance in Inspectorate General Department and Non Department. Researcher used the analytical double linier regression technique. Which also include 80 (eighty) respondents. Many researches have discussed about performance audit, but one thing which made this research different from other is the variable. Other research used variable such as ethic, perception, incentive, moral education, knowledge, independency, and the affect on auditor performance. While in this research used 4 (four) variable such as functional auditor training by BPKP (X1), Auditor competencies (X2) functional auditor (X3) and Auditor performance (Y). This research has come with the conclusion that functional auditor trained by BPKP has a strong and significant effect on the auditor performance. Auditor competencies has a strong significant to auditor performance. Auditor functional has a strong significant to auditor performance, while if it combined together the three variable X, has a very strong and significant to auditor performance. This research also has limitation such as time and budget for the research, that’s why only 80 respondent for the sample, which taken from 9 (nine) Inspectorate General and 2(two) Major Inspectorate from Non department. This sample of respondent has not satisfied enough to decide that functional auditor training by BPKP, auditor competencies and functional auditor position has a correlation to the auditor performance. That is why need a very carefully in making conclusion to this research, researcher also suggest to any similar research in the future for adding respondents and using any new variables, so the result will be more accurate and give contribution for the audit community. Key words: Auditor performance, auditor functional training by BPKP, auditor competencies, auditor functional position, analytical double linier regression technique.